Synthesis of new fluorescent amino acids with a triazolopyridine core: diacid sensors. (9th August 2018) - Chiassai, L.; Ballesteros-Garrido, R.; Ballesteros, R.; Abarca, B.
Abstract : A new family of amino acid containing pyridine–triazolopyridine cores has been prepared by means of a copper catalysed reaction. Abstract : A new family of amino acid containing pyridine–triazolopyridine cores has been prepared by means of a copper catalysed reaction. These compounds exhibit an intense emission that has been employed to sense the distance between two carboxylic acids in a linear molecule, from oxalic to glutaric acids.